Facebook marketing : an hour a day - Treadaway, Chris, 1974-; Smith, Mari, 1966- (Serious skills., 2012)
The bestselling Sybex guide to marketing on Facebook, now fully updated As the second most-visited site on the web, Facebook offers myriad marketing opportunities and a host of new tools. This bestselling guide is now completely updated to cover all of the latest tools including Deals, sponsored stories, the Send button, and more. It explains how to develop a winning strategy, implement a campaign, measure results, and produce usable reports. Case studies, step-by-step directions, and hands-on tutorials in the popular Hour-a-Day format make this the perfect handbook for maximizing marketing ef.